Evaluation of marginal and internal adaptation of fixed dental restorations on alveolar casts printed with different 3D printers. - Eidah, Rawan. (Tufts University. Tisch Library., 2024)
Thesis (M.S.)--Tufts University, 2024.; Submitted to the Tufts University School of Dental Medicine.; Advisor: Panagiotis Papaspyridakos.; Keyword: Dentistry.